Congenital CMV, Lights and Shadows on Its Management: The Experience of a Reference Center in Northern Italy - Rubinacci, Valeria; Fumagalli, Mara; Meraviglia, Giulia; Gianolio, Laura; Sala, Anna; Stracuzzi, Marta; Dighera, Anna; Zuccotti, Gian Vincenzo; Giacomet, Vania (Children (Basel), 2022)
Congenital cytomegalovirus infection (cCMV) is the most common congenital viral infection, with a consistent rate of morbidity, mortality, and long-term sequelae, especially in the case of late diagnosis. Nevertheless, a universal screening for CMV is not currently recommended, and global awareness about this infection, as well as accurate and shared indications on follow-up and treatment, are still lacking. We reviewed data about 59 suspect cCMV cases who referred to our center from 2014 to 2021. We report 41 cases of confirmed cCMV diagnosed at birth, with clinical or radiological abnormalities in 36.6% of them. Other five patients received a late diagnosis and all presented neurological impairment. Twelve patients received therapy with Valganciclovir within the first month of life, with favorable outcome in nine cases. Therapy after the first month of life was attempted in four patients, with improvement in one case. The overall awareness about cCMV infection was 32.6%. Considering our population, maternal serological screening followed by targeted testing of neonates could be an effective strategy. Some aspects of cCMV infection management should be further investigated, such as indication of treatment after the first month of life or in asymptomatic patients. Awareness about the infection should be improved to implement preventive strategies.